Efeitos de atraso em consequências culturais de magnitudes diferentes sobre a seleção de culturantes autocontrolados - LIMA, Yan Valderlon dos Santos (Universidade Federal do Pará, 2019)
Metacontingencies describe relations between culturants (interlocked behavioral contingencies with their aggregate products) and the cultural consequences which select it. If a culturant is under control of greater magnitude and delayed cultural consequences, we say that this is a self-controlled culturant. This study's objective was to evaluate the effects of delay variation on cultural consequences of different magnitudes on the selection of impulsive and self-controlled culturants. Two laboratory microcultures, each with three participants, were exposed to an experimental ABCD...n...DCBA. There was no competition between the operant and cultural levels. Participants should choose lines with numbers and colors in an array. Scheduled individual consequences were 1 and 2 tokens for even and odd choices respectively. Scheduled cultural consequences were stamps with smiley faces representing, each one, school items that were donated to a public kindergarten. The scheduled cultural consequences varied in quantity of produced school items and the delay varied in days after which these items were delivered. There was a higher frequency of self-controlled culturants in both microcultures. This study showed to be possible to investigate cultural self-control in laboratory microcultures and paves the way for new research on the subject.